Synthesis of Zinc Oxide Nanostructures Growth by the role of pH variation. Issue 1 (December 2020) - Ali, Arlina; Yusoff, Mahani; Noor, An'amt Mohamed; Teo, Pao Ter; Mamat, Sarizam; Mohamed, Mazlan; Ramli, N.H.; Akmal, Syamsyir; Rahimie,
Abstract: In this paper, we study on the morphology variation of zinc oxide (ZnO) nanostructures by varied the pH of precursor via hydrothermal method. The Zinc chloride and ammonium hydroxide were used as precursor, which was heated at 180°C for 24 hours. The pH of the precursor was varied from 7, 8, 9, 10 to 11 by the controlled amount of ammonium hydroxide. The samples were characterized with X-ray diffraction (XRD), Scanning electron microscope (SEM) and Ultraviolet-Visible (UV-Vis) spectroscopy. XRD pattern shows that the ZnO nanostructured exhibit the hexagonal wurtzite structure and average crystallite size is calculated. The morphology images revealed the rod and flower like structure for all samples. UV-Vis spectroscopy (UVs) shows the absorption or reflectance peaks of zinc oxide was around 350 to 450 nm. pH value was found key to the structure control of studied.